Computational studies on pressure distribution around a bending 5:1 rectangular cylinder - Nguyen, Dinh Tung; Hargreaves, David; Owen, John (2016)
This paper describes the development and testing of a numerical model, based around the Large Eddy Simulation model, of a flexible 5:1 rectangular cylinder. We report on the vortex-induced vibration (VIV) of the bending cylinder, which is an analogue for a flexible bridge deck. Compared with a 3D heaving sectional model, distinct differences in surface pressure distributions and Strouhal number in the span-wise direction were found. In addition, certain span-wise flow features were thought to trigger the lock-in when the flexible model underwent the bending VIV response.